Effectiveness of narrative pedagogy in developing nursing undergraduates' humanistic care ability for hospitalized children: A mixed-method study. Issue 4 (April 2023) - Liu, Fang; Yanbin Yang,; Zhou, Hengyu; Mo, Lin; Leng, Hongyao; Cui, Cui
Abstract: Background: The development of nursing students' ability to care for children is an important part of their nursing education. However, nursing students' understanding of children's experiences in healthcare is vague. The traditional lecture approach is not conducive to the cultivation of humanistic care competencies for hospitalized children. Objectives: This study aimed at exploring the effectiveness of narrative pedagogy on developing nursing students' ability to care for hospitalized children. Design: A quasi-experimental non-equivalent control group pre-test and post-test design. Setting: and participants: A purposive sampling method was used for this study. The study participants included 588 first-year nursing students in four classes at a university in western China. The students enrolled in a nursing humanistic curriculum were divided into an experimental group (295 students) and a control group (293 students). Methods: During the 5 weeks of hospitalized children's care program, the experimental group received narrative pedagogy, while the control group received traditional teaching with 2 credit hours per week. Data were collected quantitatively using the Caring Ability Inventory (CAI), as well as qualitatively through individual interviews and reflective diaries. Results: The average scores on the CAI and subscales significantly improved for both groups. As a result of controlling for the effect of pre-test scores, the experimental group had significantly higher post-test scores on the CAI than the control group. Qualitative content analysis demonstrated that narrative pedagogy enhanced nursing students' emotional experiences and facilitated their understanding of the caring practice for sick children. Conclusion: Narrative pedagogy has positive implications for improving students' care competencies for hospitalized children.